THE USE OF PODCAST TO PROMOTE STUDENTS’ SPEAKING ABILITY IN ONLINE LEARNING AT THE COVID PANDEMIC 19 - Eska Perdana Prasetya; Nuraeni Nuraeni (STKIP Persada Khatulistiwa Sintang, 2021)
The objective of this research was to promote students' speaking ability by using podcasts in teaching and learning. the subject of the research was taken in one of the senior high schools in Bogor 11th grades and the participant was 6 students consists 3 of females and 3 of males. The method used in this study was Classroom Action Research (CAR), conducted in two cycles. The phases are planning, acting, observing, and reflecting as the process of teaching and learning. For collecting the data the researcher used the quantitative data that were obtained from the documents, observations, and interviews to investigate the students' promotion in speaking ability such a promoting their grammar, pronunciation, vocabulary, and self-confidence. It can be concluded that the students' speaking ability could be promoted by using podcasts in English teaching and learning.Keywords:Podcasts, Promote,Speaking,Online Learning